Coronavirus (Covid-19) Impact on Working Capital of Small and Medium-Scale Enterprises (Smes) in Nigeria - Mary Josiah; Yemisi Bosun – Fakunle; Gbenga Ekundayo; Festus Odhigu (Asian Journal of Finance & Accounting, 2024)
The outbreak of corona virus has resulted in a global health emergency, and global economic slowdown, this is a challenge to SMES, because this advanced down the whole world. This research has been carried out to investigate the impact of covid 19 on working capital of small and medium scale enterprise in Nigeria. Survey research design was adopted during the course of the study As part of this study, comprehensively structured questionnaires were distributed to the respondents in order to get relevant information associated with the research. 378 questionnaires were distributed and 370 were returned. The data collected were analyzed using multivariate test. The results show that Covid-19 has a statistically significant negative effect on all the working capital variables of small and medium enterprises under the study (inventory, receivables, payables and cash). In the light of this, the Nigerian Government should set up an evaluation committee that will look into these negative effects of covid 19 on SMEs and provide assistance so as to guarantee the continuity of those businesses.